Witnessing Obstetric Violence during Fieldwork: Notes from Latin America - Arachu Castro (Harvard FXB Center for Health and Human Rights, 2019)
Violence against women in labor occurs frequently in Latin America, based on observations from my extensive ethnographic fieldwork in various Latin American countries. In this article, focused on Mexico and the Dominican Republic, I contextualize obstetric violence within the larger context of social exclusion and discrimination against women. I establish associations between maternal deaths and health care systems characterized by a lack of continuum of care, a lack of accountability toward women, and the withholding of care. I argue that clinical staff learn to operate within the structural limitations of health care systems by not assuming the responsibility of the continuum of care that each woman needs, and that this discharge of accountability is at the heart of how health professionals can navigate, tolerate, and perpetuate the structure of the system and, in so doing, create the breeding ground for obstetric violence to occur. Finally, I explain that although reporting on the suffering of women will not, on its own, prevent obstetric violence, increasing its visibility through research can contribute to human rights-based advocacy on behalf of women in labor, to the monitoring of human rights standards, and to the creation of accountability measures within health systems to prevent obstetric violence.